Transverse Analysis of Box Girders with Corrugated Steel Webs - Fen Xu; Yikai Cheng; Kangjian Wang; Man Zhou (Buildings, 2024)
The utilisation of box girders with corrugated steel webs (CSWs) represents an innovative approach to bridge superstructure design that has garnered substantial popularity worldwide, with a notable prevalence in both Asia and Europe. Compared with traditional box girders, they avoid web cracking, improving the prestressing efficiency and bridge spanning ability. As an innovative box girder, a corrugated web can increase the cantilever length and transverse stiffness, and at the same time, it reduces the dead weight of the bridge deck. However, little research has been conducted on the mechanical properties of this novel spine-like box girder with CSWs, especially its transverse performance, although it has been used in many applications. In this paper, the effect of the web form on the behaviour of box girders is introduced. Therefore, three representative three-dimensional (3D) finite-element models (i.e., corrugated web box girder, flat web box girder, and ordinary equivalent concrete web box girder) have been established to quantitatively investigate the influence of corrugated web stiffness on transverse stress under the action of gravity and vehicle loads. Generally, significant differences in the mechanical performance of box girders with CSWs have been observed compared with conventional box girders with concrete webs. Additionally, parametric studies to investigate the influences of the corrugation dimensions (in term of the corrugation height, web thickness, panel width, web height and elastic modulus) on the transverse stiffness of such bridges are analyzed. The results show that a new stiffness formula can be put forward to consider the effect of web height, and a high-strength steel web needs to be developed urgently for box girders with CSWs in the near future. Overall, the results of this investigation can be used as a reference for transverse designing and segmental construction of similar projects.